สมบัติ เสถียรภาพ และสภาพสลายได้ทางชีวภาพของฟิล์มโปรตีนถั่วเหลืองสกัดเสริมเส้นใยเซลลูโลส - นันทพร โพธิวุฒิคุณ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Soy protein is one of the biopolymers that can be used for fabricating bio-degradable film. Soy protein film, however, still has limitation in terms of mechanical strength. Fiber reinforcement is one technique that could be used to improve mechanical property of various materials. Being high in strength and bio-degradable, cellulosic fibers are thus good candidate for using as reinforcing agent in bio-degradable films. This research aimed to investigate the effect type, particle size, and content of cellulosic fibers on properties, stability and bio-degradability of soy protein isolate film. Two types of cellulosic fibers (cellulose and microcrystalline cellulose) were varied in terms of particle size (20 and 50 µm) and content (5, 10 and 15% by weight of protein). Regarding to mechanical properties, fiber reinforcement was found to pose an effect on tensile strength, especially for those samples reinforced with 20 µm microcrystalline cellulose which exhibited significantly higher tensile strength than the control (p≤0.05). In contrast, elongation at break was found to decrease with increasing fiber content. Fiber reinforcement was shown to induce a decrease in film transparency and an increase in water vapor permeability and contact angle between water droplet and the film surface. Fiber-containing films demonstrated decreasing L* and increasing a* and b*. All samples possessed a hue angle of about 90°, representing yellow color. Chroma was found to increase with increasing fiber content. Pertaining to film morphology, the fiber-containing films possessed increasing surface roughness and reduced matrix homogeneity. For film stability, it was found that type and particle size of cellulosic fiber did affect water solubility. The films with 20 µm-fiber were less soluble than those with 50 µm-fiber. On the other hand, the cellulose-added films exhibited lower solubility than those added with microcrystalline cellulose. From the sorption behavior at 25 °C, all film samples demonstrated similar isotherm shape. In general, the film samples had decreasing tensile strength and increasing elongation at break with increasing water activity. Similar thermal degradation profiles were observed for the control and those with cellulosic fiber. Three regions of mass loss were revealed with water evaporation occurring in the temperature range of 80-120 ̊C, volatilization of glycerol occurring in the temperature range of 180-260 ̊C, and degradation of protein and cellulosic fiber occurring in the temperature range of 300-320 ̊C. Bio-degradability as determined using aerobic bio-degradation under controlled composting condition unveiled that the film containing 20 µm-microcrystalline cellulose at 15% concentration demonstrated 86.97% bio-degradation, which was similar in value to the control which demonstrated 85.43% bio-degradation.